To Compare the Morbidity and Mortality Pattern of late Preterm and Term Neonates at GRMC, Gwalior - Neetu Sharma; Manish Rathore (Asian Journal of Clinical Pediatrics and Neonatology, 2019)
Background: This is a hospital based prospective observational study, carried out at Gajara Raja Medical College, Gwalior. All the inborn late preterm babies have been included in the study. Selection of late preterm neonates is done by determination of gestational age.Subjects and Methods:All the inborn late preterm babies have been included in the study. Selection of late preterm neonates is done by determination of gestational age. We compared the mortality and morbidity pattern of preterm neonates with the term counterpart, the data of term neonates retrieved from hospital record.Results:Maximum no. of cases in late preterm in Jaundice i.e. 9%, followed by Septicaemia 7.8% &Respiratory Distress 7.6%. In Term Jaundice i.e. 3.34%, followed by Septicaemia 3.38% &Respiratory Distress 3.41%. In our study Neonatal convulsions were more common among the late preterm neonates as compare to term group.Conclusion:In our study jaundice, septicemia, respiratory distress and hypoglycemia were found as major morbidities, among late preterm the rate was found to be 9%,7.8%,7.6% and 6% respectively while in term group the rate was 3.34%, 3.38%, 3.41% and 2.56% respectively.The mortality and morbidity among late preterm neonates were higher as compared to their term counterparts, implying the need for special attention to these babies because they may be overlooked among other preterm and sick babies.